Brain protection during aortic arch surgery: current state of problem - D. V. Khomushku; D. A. Sirota; A. A. Shadanov; A. G. Edemskiy; A. M. Chernyavskiy (Вестник хирургии имени И.И. Грекова)
Aortic arch surgery is one of the most challenging field of cardiovascular surgery. Reconstructive interventions on the aortic arch are associated with high risks due to the peculiarities of anatomy and technical complexity of surgical intervention. Antegrade cerebral perfusion in combination with hypothermia is widely used to protect the brain during aortic arch surgery. Antegrade cerebral perfusion can be performed in unilateral or bilateral way. Now, there is no clear guidelines regarding the management of patients operated on the aortic arch. This review highlights the main methods of protecting the brain during aortic arch surgery and shows the results of the studies comparing antegrade unilateral brain perfusion with bilateral one. We reviewed rationale of various researchers in choosing two proposed methods to reduce the risk of neurological complications.